2014
DOI: 10.1371/journal.pone.0107965
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Malaria in Children Aged 0-2 Years: The Role of Foetal Haemoglobin and Maternal Antibodies to Two Asexual Malaria Vaccine Candidates (MSP3 and GLURP)

Abstract: BackgroundChildren below six months are reported to be less susceptible to clinical malaria. Maternally derived antibodies and foetal haemoglobin are important putative protective factors. We examined antibodies to Plasmodium falciparum merozoite surface protein 3 (MSP3) and glutamate-rich protein (GLURP), in children in their first two years of life in Burkina Faso and their risk of malaria.MethodsA cohort of 140 infants aged between four and six weeks was recruited in a stable transmission area of south-west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 54 publications
2
47
1
Order By: Relevance
“…While seasonality and parasite density have been considered in some studies (39)(40)(41), antimalarial usage, microscopy or polymerase chain reaction detection methods and varying duration between initial detection of parasites and onset of symptoms ranging from three to twenty-one days, have also been used to define malaria in other studies (5,21,42). Consequently, the profiles obtained for infants in this study could change if our definitions followed any of the above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While seasonality and parasite density have been considered in some studies (39)(40)(41), antimalarial usage, microscopy or polymerase chain reaction detection methods and varying duration between initial detection of parasites and onset of symptoms ranging from three to twenty-one days, have also been used to define malaria in other studies (5,21,42). Consequently, the profiles obtained for infants in this study could change if our definitions followed any of the above.…”
Section: Discussionmentioning
confidence: 99%
“…The low incidence of symptomatic malaria below six months of age has been attributed to presence of fetal hemoglobin (14,15) and passively acquired maternal IgG (16). Also, malaria-specific antibodies at birth (in maternal and/or cord blood) have been associated with protection against some malaria parasite antigens but not others (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Demonstration of in-vitro malaria parasite growth inhibitory characteristics of lactoferrin and immunoglobin A (IgA) found in breast milk as well as maternal and infant sera has led others to hypothesize that infants are protected from malaria [8,9]. The assumption of infant's immunity against malaria was further boosted by studies that showed that high hemoglobin F concentration at birth inhibits malaria parasite's development in the first few months of human life [10,11]. This assumption of a sixmonth period of protection in a newborn in contradicted by other studies which found no relationship between presence of maternal antibodies and their protection against malaria in African infants [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The assumption of infant's immunity against malaria was further boosted by studies that showed that high hemoglobin F concentration at birth inhibits malaria parasite's development in the first few months of human life [10,11]. This assumption of a sixmonth period of protection in a newborn in contradicted by other studies which found no relationship between presence of maternal antibodies and their protection against malaria in African infants [11,12]. Several other studies undertaken in health facilities and communities in some sub-Saharan countries showed a higher burden of disease in infants under 6 months than what is generally assumed and even if the antibodies provide some protection, it is shorter than the widely quoted six months [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…All these have failed in field trials as single antigen vaccines, suggesting a need for combinatorial vaccines that target multiple antigens present at different stages of the parasite's development (Schwartz et al, 2012, Tham et al, 2012. ME-TRAP combined with MSP-1 failed to significantly induce protection (Hodgson et al, 2014), nevertheless, the fused vaccine comprising of P. falciparum glutamate-rich protein (PfGLURP) and MSP-3 was able to induce cytophilic antibodies which affected parasite development (Kangoye et al, 2014, Baumann et al, 2012, Tamborrini et al, 2011. With all these parasite ligands, there are still limited numbers of recombinant or vectored vaccine candidates that have been shown to be efficacious in clinical trial (Hill, 2011.…”
Section: It Has Been Established For Over 40 Years Now That Immunizatmentioning
confidence: 99%